Efforts to Release an Intelkam Unit to Prevent Conflict Between Silat Colleges in the Jurisdiction of the Madiun City Police - Siswanto, Innigo Umar (Police Studies Review, 2024)
Raising efforts are a form of activity carried out by the Intelkam unit to create ideal social security conditions. However, in its implementation, the fundraising efforts carried out by the Intelkam unit were deemed to have not been successful in preventing conflict between silat schools in the jurisdiction of the Madiun City Police. This is proven by the fact that there are still cases of conflict between silat schools that occur in the jurisdiction of the Madiun City Police every year. A qualitative approach was used in this research to gain an understanding of "efforts to mobilize intelligence and security units to prevent conflict between silat schools in the Madiun City Police jurisdiction" in its implementation by the Madiun City Police Intelligence and Security unit. The type of research used is field research which is carried out by collecting information obtained from respondents through structured interviews. This research also uses theories and concepts that are in line with the research title, including Management Theory, Intelligence Concept, Intelligence and Security Creation Concept, and Conflict Concept. The results of the research found that there were deficiencies in implementation management and management of organizational resources, such as the non-neutrality of members who took part in carrying out fundraising in the field and incompatibility between the implementation of fundraising in the field and the existing fundraising procedures in Perkabik number 1 of 2023. However, the reverse is true. These deficiencies include things that support the continued implementation of fundraising, such as adequate facilities and infrastructure and a budget that can be distributed properly.